Rare or Rarely-Used PUs as Descriptors of Literary Style. Aspects of Ausiàs March's UFs Based on Corpus Linguistics and Translations. - MARTINES, VICENT (Scripta, 2023)
Paying attention to the frequency of use is also a key aspect in the characterization of literary style. In this case, the linguistic resources utilized by authors are important because they contextualize them within their time, context, and cultural movement. Rare linguistics elements are not less relevant, that is those used only by one or a few authors. We analyze examples that confirm the methodological relevance of Corpus Linguistics, translation and analysis of PUs so that we can better understand what makes Catalan classics unique in what referes to their verbal art. To do so, we focus on UPs -[verbal] locutions-with rare occurrences and in some cases with only 1 or 2 occurrences (or up to 5, always in a few authors or even in one single author). We have analyzed examples of single (or rare) occurrences of the great Valencian poet Ausiàs March.